2015
DOI: 10.3389/fmicb.2015.00524
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of extracellular proteins expressed by various clonal types of Staphylococcus aureus and during planktonic growth and biofilm development

Abstract: Staphylococcus aureus is well known for its biofilm formation with rapid emergence of new clones circulating worldwide. The main objectives of the study were (1) to identify possible differences in protein expression among various and closely related clonal types of S. aureus, (2) to establish the differences in protein expression in terms of size of protein spots and its intensities between bacteria which are grown statically (biofilm formation) with that of under aeration and agitation, and (3) to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Limitations of this study consist of the clinical translatability of the results, including biofilm maturation and heterogeneity, biofilm quantification methods, the size, and shape of the coupons as compared to prosthetics, the duration of treatment exposure, and the cytotoxicity of these topical adjuvants to healthy cells. Although it has been shown that mature biofilm can be established in vitro following 48 h incubation, clinical presentations of biofilm‐related joint infection generally consist of long‐established biofilm . However, the clinical application of adjuvant treatments as described here would be considered in the setting of acute infections.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this study consist of the clinical translatability of the results, including biofilm maturation and heterogeneity, biofilm quantification methods, the size, and shape of the coupons as compared to prosthetics, the duration of treatment exposure, and the cytotoxicity of these topical adjuvants to healthy cells. Although it has been shown that mature biofilm can be established in vitro following 48 h incubation, clinical presentations of biofilm‐related joint infection generally consist of long‐established biofilm . However, the clinical application of adjuvant treatments as described here would be considered in the setting of acute infections.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant P. acnes proteins were identified to be CAMP factors, and surface‐exposed dermatan sulfate adhesions [47]. The variation in protein expression of different clonal types of S. aureus at various stages of biofilm formation was determined by coupling 2D gel electrophoresis and LC‐MS/MS [48]. The differentially expressed proteins of Dunaliella salina , a halotolerant organism, were identified by MALDI‐TOF/TOF as molecular chaperones and proteins involved in respiration, photosynthesis, and amino acid synthesis [49].…”
Section: Techniques To Study Comparative Proteomicsmentioning
confidence: 99%
“…The antagonistic properties of LAB seem to be attractive also for targeting pathogens in biofilm embedded forms [11][12][13][14]. Biofilm is a complex three-dimensional microbial consortium where bacteria are embedded in an extracellular matrix of organic polymers produced by bacteria themselves [15][16][17]. The matrix drastically reduces the susceptibility of bacteria to different outer stress factors [18] providing up to 1000-fold higher tolerance to antimicrobials of the biofilm-embedded cells compared to their planktonic counterparts [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%